Respuesta :

Answer:

Right 3, Down 4

Step-by-step explanation:

Given

[tex]f(x) = x^2[/tex]

[tex]g(x) = (x + 3)^2 - 4[/tex]

Required

The transformation from f(x) to g(x)

When a function is translated up by h units, the rule is:

[tex](x,y) \to (x + h,y)[/tex]

So, we have:

[tex]f'(x) = (x + h)^2[/tex]

By comparison, h = 3. So:

[tex]f'(x) = (x + 3)^2[/tex]

When a function is translated down by h units, the rule is:

[tex](x,y) \to (x,y - h)[/tex]

So, we have:

[tex]g(x) = f'(x) -h[/tex]

By comparison, h = 4. So:

[tex]g(x) = (x + 3)^2 - 4[/tex]

Hence, the transformation is: 3 units right and 4 units down